Immunological profile and its clinical implications in pediatric infectious mononucleosis - Wang, Jie; Zhao, Xinfeng; Ye, Cuiying; Xu, Xudong (Frontiers in Pediatrics, 2025)
ObjectiveTo analyze the differences in peripheral blood immune function between children with infectious mononucleosis (IM) who developed liver injury (LI) and those non-liver injury (NLI), and to investigate the regulatory role of immune markers in IM infection.MethodsA total of 50 hospitalized children diagnosed with IM at Hangzhou Children's Hospital between November 2023 and August 2024 were enrolled as the Epstein–Barr Virus (EBV) infection group, including 19 without LI and 31 with LI. Additionally, 30 age-matched healthy children undergoing routine physical examinations during the same period were included as the control group. Flow cytometry was used to detect 12 cytokines, granzyme B (GzmB), perforin (PRF), regulatory T cells (Tregs), programmed cell death protein 1 (PD-1), and other immune markers in peripheral blood. CD100 levels were measured by ELISA.ResultsThe expression levels of IL-5, IFN-α, IL-2, IL-6, IL-10, IFN-γ, and IL-8 were significantly elevated in the EBV infection group compared to the control group (P < 0.01). Expression of GzmB and PRF in CD3+ and CD8+ T lymphocytes was significantly higher in the EBV group than in controls (P < 0.05). PD-1 and CD100 were also elevated in the EBV group (P < 0.01). Conversely, the expression of Tregs, CD28 in CD3+ and CD8+ T lymphocytes was significantly lower in the EBV group than in the control group (P < 0.01). Further comparison between the LI and non-liver injury (NLI) subgroups revealed that GzmB levels in CD3+ and CD8+ T lymphocytes were significantly higher in the LI group, while CD28 expression in CD3+ and CD8+ T lymphocytes was lower in the LI group compared to the NLI group (P < 0.05). Correlation analysis showed that PRF, PD-1 expression in CD3+ and CD8+ T lymphocytes, and IL-10 levels were positively correlated with EBV-DNA load (P < 0.05). GzmB in CD3+ and CD8+ T lymphocytes and IFN-γ levels were positively correlated with body temperature (P < 0.05). CD28 expression in CD3+ and CD8+ T lymphocytes was negatively correlated with ALT levels (P < 0.05).ConclusionEBV infection-induced IM is associated with abnormal expression of various immune markers in peripheral blood.The high expression of GzmB and low expression of CD28 are associated with LI in IM.